Solubility of carbon dioxide in aqueous solutions of Piperazine (PZ) at elevated pressures - Murshid, G. (Trans Tech Publications Ltd, 2014)
The solubility of carbon dioxide (CO2) was measured in (0.2, 0.4, 0.6 & 1.2) molars of aqueous solutions of Piperazine (PZ) at three temperatures (30, 40 and 60)Â°C. The measurements were made over the pressure range of 5 to 60 bar. The results are presented as a function of pressure. It has been found that PZ gives significantly higher CO2 loadings at higher pressures. The influence of pressure on solubility is found to be positive. However, solubility decreases with the increase of temperature and PZ concentration. Â© (2014) Trans Tech Publications, Switzerland.